The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/elan.202060578
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Silane‐based Self‐assembled Monolayers Deposited on Fluorine Doped Tin Oxide as Model System for Development of Biosensors for Toxin Detection

Abstract: In this work mixed hybrid phospholipid bilayers (mhBLM) were deposited on fluorine doped tin oxide (FTO) films. Two component silane‐based self‐assembled monolayers (SAMs) formed on FTO surface trigger vesicle fusion and formation of mhBLMs which are stable, can be easily regenerated, and therefore, used for multiple experiments. We found that certain chemical and physical conditions under which mixed SAMs are fabricated translate into functional properties of mhBLMs. In all cases we observed interaction of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…4, properties of mhBLM does not change over 18 h. Previously, a similar experiment was carried out using methyltrichlorosilane (MTS) as a backfiller [14]. The authors showed (see supporting information [14]) that the membrane is stable over hours and pore forming toxins can be incorporated into the membrane. Therefore, mhBLMs obtained in this study can be applied for the incorporation of pore forming toxins as well.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…4, properties of mhBLM does not change over 18 h. Previously, a similar experiment was carried out using methyltrichlorosilane (MTS) as a backfiller [14]. The authors showed (see supporting information [14]) that the membrane is stable over hours and pore forming toxins can be incorporated into the membrane. Therefore, mhBLMs obtained in this study can be applied for the incorporation of pore forming toxins as well.…”
Section: Resultsmentioning
confidence: 91%
“…During the hydrolysis reaction between silane and oxide surface strong Si-O-Sn bonds are formed which contribute to robust SAM formation [13]. One important advantage of silanised oxide surfaces is suitability for multi-cycle hybrid bilayer lipid membrane formation and regeneration [4,6,14,15], particularly due to the strength of the Si-O-Sn bond. In contrary, for the gold/ alkylthiol system, the phospholipid bilayer could not be immobilised several times because a mixed monolayer rearranges to packed islands of long alkylchain molecules up to 72 h exposure to an aqueous solution [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Transmembrane proteins (vaginolysin, 56, 8 kDa) could not penetrate such rigid structure therefore, in further studies, long alkylchain OTS was diluted with methyltrichlorosilane (MTS), in order to produce less hydrophobic and less rigid SAM. 24 Relatively small peptide melittin (2, 6 kDa) did penetrate the membrane however, the lack of space between the solid support and the lipid bilayer, impeded reconstitution of α-hemolysin (33 kDa) to the membrane.…”
Section: Supplementary Materials For This Article Is Available Onlinementioning
confidence: 99%
“…In general most of the metal oxide semiconductors (MOS) such as RuO 2 [9,10], NiO [11], SnO 2 [12], MnO 2 [13,14], Fe 3 O 4 [15], CuO [16], ZnO [17], and CoO [18] are having a significant contribution for the SC applications [19]. Tin oxide (SnO 2 ) is well-known among MOS due to its vast applications such as in gas sensors [20,21], biosensors [22,23], solar cells [24,25], Li-ion battery materials [26,27], photocatalytic applications [28],…”
Section: Introductionmentioning
confidence: 99%